Models of the anti-corruption "compliance control" system in foreign countries and their specific aspects: The example of the US and UK legislation (Zien Journal of Social Sciences and Humanities, 2022)
The article includes the necessity of creating an anti-corruption "compliance-control" system, its international models, specific features of the system, positive achievements of implementation in the private sector, and scientific and comparative analyzes of legal norms in this direction, on the example of the legislation of the USA and Great Britain